Impaired autophagy with augmented apoptosis in a Th1/Th2-imbalanced placental micromilieu is associated with spontaneous preterm birth - Akram, Khondoker M.; Frost, Lucy I.; Anumba, Dilly OC. (Frontiers in Molecular Biosciences, 2022)
Background: Despite decades of research, the pathogenesis of spontaneous preterm birth (PTB) remains largely unknown. Limited currently available data on PTB pathogenesis are based on rodent models, which do not accurately reflect the complexity of the human placenta across gestation. While much study has focused on placental infection and inflammation associated with PTB, two key potentially important cellular events in the placenta - apoptosis and autophagy - remained less explored. Understanding the role of these processes in the human placenta may unravel currently ill-understood processes in the pathomechanism of PTB. Methods: To address this necessity, we conducted qRT-PCR and ELISA assays on placental villous tissue from 20 spontaneous preterm and 20 term deliveries, to assess the inter-relationships between inflammation, apoptosis, and autophagy in villous tissue in order to clarify their roles in the pathogenesis of PTB. Results: We found disrupted balance between pro-apoptotic BAX and anti-apoptotic BCL2 gene/protein expression in preterm placenta, which was associated with significant reduction of BCL2 and increase of BAX proteins along with upregulation of active CASP3 and CASP8 suggesting augmented apoptosis in PTB. In addition, we detected impaired autophagy in the same samples, evidenced by significant accumulation of autophagosome cargo protein p62/SQSTM1 in the preterm villous placentas, which was associated with simultaneous downregulation of an essential autophagy gene ATG7 and upregulation of Ca2+-activated cysteine protease CAPN1. Placental aggregation of p62 was inversely correlated with newborn birth weight, suggesting a potential link between placental autophagy impairment and fetal development. These two aberrations were detected in a micromilieu where the genes of the Th2 cytokines IL10 and IL13 were downregulated, suggesting an alteration in the Th1/Th2 immune balance in the preterm placenta. Conclusion: Taken together, our observations suggest that impaired autophagy and augmented apoptosis in a Th1/Th2 imbalanced placental micro-environment may be associated with the pathogenesis of spontaneous PTB.